Tamil cinema: culture politics of india's other film industry/ edited by Selvaraj Velayutham - Velayutham,Selvaraj (Ed.) (London, 2008)
Hitherto, the academic study of Indian cinema has focused primarily on Bollywood, despite the fact that the Tamil film industry, based in southern India, has overtaken Bollywood in terms of annual output. This book examines critically the cultural and cinematic representations in Tamil cinema. It outlines its history and distinctive characteristics, and proceeds to consider a number of important themes such as gender, religion, class, caste, fandom, cinematic genre, the politics of identity and diaspora. Throughout, the book cogently links the analysis to wider social, political and cultural phenomena in Tamil and Indian society. Overall, it is an exciting and original contribution to an under-studied field, also facilitating a fresh consideration of the existing body of scholarship on Indian cinema.
Keywords: Motion picture industry-India-Tamil Nadu